(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In today’s competitive market, businesses are increasingly realizing the value of cultivating and successfully maintaining customer relationships. Organizations must understand and fulfill the expectations of their customers in order to establish and maintain a good relationship with them. Today’s businesses should concentrate not just on pleasing their customers, but also on delighting them. As a result, it has become critical for businesses to identify and assess the factors that lead to customer happiness or discontent in order to make the required adjustments based on consumer perceptions. Service quality, customer satisfaction, the relationship between service quality and customer satisfaction, service quality management (SQM) in Indian railroads, and the service quality gap are all discussed in this research. The study’s emphasis is on service quality models.